Concordance Test Between Dermoscopic and Histopathological Parameteres in Basal Cell Carcinoma - Hartanto, Felix; Kusumaputra, Bagus Haryo; Sari, Maylita; Citrashanty, Irmadita; Mappamasing, Hasnikmah; Astari, Linda; Sandhika, Willy; Hidayati, Afif Nurul; Prakoeswa, Cita Rosita Sigit; Listiawan, Muhammad Yulianto (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Basal cell carcinoma (BCC) is the most common skin cancer and can cause local tissue damage. BCC can occur in all populations, regardless of skin color. Dermoscopy has compatibility with histopathology in determining the benign or malignant nature of a lesion. Dermoscopy can improve the diagnostic accuracy of BCC by >90%, with 7 parameters that can be found: arborizing vessels, blue-gray ovoid nests, blue-gray dots/globules, maple leaf-like areas, spoke-wheel areas, ulceration, and hiny white areas. Purpose: To assess the compatibility of each dermoscopy parameter with its corresponding histopathological parameters. Methods: Observational analytic study with a cross-sectional approach was performed. Dermoscopy parameters were obtained by reassessing all photographs, while histopathological parameters were obtained from pre-existing slide reviews. Cohen's Kappa test was performed to analyze both variables. Result: A Total of 26 samples met the inclusion criteria. Most BCCs were found in female sex (65.4%), age >50 years (80.8%), and facial location (88.5%). Cohen's Kappa test was significant in 2 out of 7 dermoscopy parameters: